Prognostic implication of right ventricular dysfunction and tricuspid regurgitation following transcatheter aortic valve replacement. Issue 5 (7th March 2021) - Granot, Yoav; Merdler, Ilan; Finkelstein, Ariel; Arbel, Yaron; Banai, Shmuel; Topilsky, Yan; Scwartz, Lorin Arie; Segev, Amit; Barbash, Israel; Fefer, Paul; Danenberg, Haim; Shuvy, Mony; et al.
Abstract: Objectives: Right ventricular (RV) dysfunction and tricuspid regurgitation (TR) are associated with adverse outcomes in severe aortic stenosis (AS) patients. Our aim was to evaluate the association between ≥moderate TR and RV dysfunction on long‐term mortality following transcatheter aortic valve replacement (TAVR). Methods: A retrospective analysis of the Israeli multicenter TAVR registry among 4, 344 consecutive patients, with all‐cause mortality as the main outcome measure. Results: Echocardiographic assessment of TR grade and RV dysfunction was available for 3, 733 and 1, 850 patients, of whom ≥moderate TR and RV dysfunction was noted for 478(13%) and 78(4%), respectively. The mean follow‐up time was 2.9 ± 2.3 years. In univariate models, ≥Moderate TR and ≥moderate RV dysfunction were associated with increased long‐term mortality (HR 1.45, 95% CI 1.24–1.69, p  < .001 and HR 1.73, 95% CI 1.21–2.47, p  = 0.003, respectively). These finding did not remained significant after adjusting to echocardiographic parameters. A subset of patients with no improvement in RV function had the highest long‐term mortality risk (HR 3.3, 95% CI 1.95–5.7, p  < .001). Conclusion: When adjusted to multiple echocardiographic characteristics baseline ≥Moderate TR and ≥moderate RV dysfunction were not associated with long‐term mortality following TAVR. Persistent RV dysfunction following TAVR was associated with the highest risk for mortality.